Thin panels of cement composites reinforced with recycled fibres for the shear strengthening of reinforced concrete elements - Zamanzadeh, Ziaaddin (2015)
A new technique was developed for producing thin panels of a cement based material reinforced with relatively high content of steel fibres originated from the industry of tyre recycling. Flexural tests with notched and un-notched specimens were carried out to characterize the mechanical properties of this Fibre Reinforced Cement Composite (FRCC) and the results are presented and discussed. The values of the fracture mode I parameters of the developed FRCC were determined by performing inverse analysis with test results obtained in three point notched beam bending tests. To appraise the potentialities of these FRCC panels for the increase of the shear capacity of reinforced (RC) beams, numerical research was performed on the use of developed FRCC panel for shear reinforcement by applying the panels in the lateral faces of RC beams deficiently reinforced in shear.